Integrating Multimodal Artificial Intelligence in Qur'anic Education: Architecture, Technical Precision, and Pedagogical Efficacy - Fatih, Muhammad Iqbal Al; Salim, Hakimuddin; Ali, Mohamad (Universitas Muhammadiyah Surakarta, 2025)
Objective: This research systematically investigates the integration of Artificial Intelligence (AI) to facilitate personalized learning pathways in Qur'anic education, focusing on phonetic accuracy (tajwid) and student engagement. The study aims to bridge the gap between traditional instruction and modern